2012
DOI: 10.1097/dad.0b013e31823067f8
|View full text |Cite
|
Sign up to set email alerts
|

Composite B-cell and T-cell Lineage Post-transplant Lymphoproliferative Disorder of the Lung with Unusual Cutaneous Manifestations of Mycosis Fungoides

Abstract: We present the case of a 17-year-old male kidney transplant recipient who presented initially with dermatologic symptoms and was found to have histologic changes in the skin that were consistent with mycosis fungoides. Shortly after this diagnosis was made, imaging studies demonstrated multifocal interstitial and airspace consolidation in both lungs. Physical examination revealed no lymphadenopathy or hepatosplenomegaly, but an open lung biopsy revealed an Epstein-Barr virus (EBV)-negative monomorphic T-cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A single center study 209 showed that the incidence of PTLD in general was 0.8% for bone marrow transplants, 1.4% for renal, 1.8% for cardiac, 4.5% for lung, but up to 10% for combined cardiac and lung transplant recipients. Since the latter type of transplants are more frequently used in children with congenital anomalies, cutaneous PTLD have been reported with some frequency in childhood 152,210,211 . The data about the incidence of cutaneous PTLD is sparse and a study from two transplant centers in France reported 7.5 primary cutaneous PTLD/1000 total primary cutaneous lymphomas/year, and 0.7 cutaneous PTLD/1000 solid organ transplants/year 212 .…”
Section: Cutaneous Post-transplant Lymphoproliferative Disorders (Ptld)mentioning
confidence: 99%
“…A single center study 209 showed that the incidence of PTLD in general was 0.8% for bone marrow transplants, 1.4% for renal, 1.8% for cardiac, 4.5% for lung, but up to 10% for combined cardiac and lung transplant recipients. Since the latter type of transplants are more frequently used in children with congenital anomalies, cutaneous PTLD have been reported with some frequency in childhood 152,210,211 . The data about the incidence of cutaneous PTLD is sparse and a study from two transplant centers in France reported 7.5 primary cutaneous PTLD/1000 total primary cutaneous lymphomas/year, and 0.7 cutaneous PTLD/1000 solid organ transplants/year 212 .…”
Section: Cutaneous Post-transplant Lymphoproliferative Disorders (Ptld)mentioning
confidence: 99%